Prevalence of cervical cytological abnormalities in Turkey - Kara, Fadil; Kiran, Guerkan; Metindir, Jale; Ozan, Hakan; Ozalp, Sinan; Vardar, M. Ali; Sam, Asli Demir (Wiley, 2009)
Objective: To evaluate retrospectively the prevalence of cervical cytological abnormalities in patient records obtained from healthcare centers in Turkey. Method: Demographic characteristics and data on cervical cytological abnormalities were evaluated from patients who underwent flap tests in healthcare centers in 2007. Results: Data were collected from 33 healthcare centers totaling 140 334 patients. Overall, the prevalence of cervical cytological abnormalities was 1.8%; the prevalence of ASCUS, ASC-H, LSIL, HSIL, and AGC was 1.07%, 0.07%, 0.3%, 0.17%, and 0.08%, respectively. The prevalence of preinvasive cervical neoplasia was 1.7% and the prevalence of cytologically diagnosed invasive neoplasia was 0.06%. Conclusion: The abnormal cervical cytological prevalence rate in Turkey is lower than in Europe and North America. This might be due to sociocultural differences, lack of population-based screening programs, or a lower HPV prevalence rate in Turkey. (C) 2009 International Federation of Gynecology and Obstetrics. Published by Elsevier Ireland Ltd. All rights reserved.
Keywords: Cervical cancer; Cervical cytology; Cervical intraepithelial neoplasias; Cervical neoplasias; Pap test; Pap smear; Turkey